2013
DOI: 10.1016/j.cmet.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The REGγ Proteasome Regulates Hepatic Lipid Metabolism through Inhibition of Autophagy

Abstract: SUMMARY The ubiquitin-proteasome and autophagy-lysosome systems are major proteolytic pathways, whereas function of the Ub-independent proteasome pathway is yet to be clarified. Here, we investigated roles of the Ub-independent REGγ-proteasome proteolytic system in regulating metabolism. We demonstrate that mice deficient for the proteasome activator REGγ exhibit dramatic autophagy induction and are protected against high-fat diet (HFD)-induced liver steatosis through autophagy. Molecularly, prevention of stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 45 publications
3
78
0
Order By: Relevance
“…Proteasome activators may recruit distinct substrates for proteasomal degradation thereby facilitating cellular recovery after protein stress. In line with this concept, both, PA28␥ and PA200, have been shown to target specific proteins for degradation via the 20S core particle: steroid receptor coactivator-3 (SRC-3), cyclin-dependent kinase inhibitors p16, p19, and p21, as well as the deacetylase SIRT1 have been identified as substrates for PA28␥-containing alternative com-plexes (6,19,20,54). Moreover, PA28␥ was shown to be involved in ubiquitin-dependent proteasomal degradation of p53 (61,62).…”
Section: Discussionmentioning
confidence: 79%
“…Proteasome activators may recruit distinct substrates for proteasomal degradation thereby facilitating cellular recovery after protein stress. In line with this concept, both, PA28␥ and PA200, have been shown to target specific proteins for degradation via the 20S core particle: steroid receptor coactivator-3 (SRC-3), cyclin-dependent kinase inhibitors p16, p19, and p21, as well as the deacetylase SIRT1 have been identified as substrates for PA28␥-containing alternative com-plexes (6,19,20,54). Moreover, PA28␥ was shown to be involved in ubiquitin-dependent proteasomal degradation of p53 (61,62).…”
Section: Discussionmentioning
confidence: 79%
“…GFP-tagged REGγ deletion mutants were kindly provided by Dr. Chuangui Wang (East China Normal University, Shanghai, China). 11 Lentivirus vectors were produced by subcloning REGγ and its mutants into PLVX-ZsGreen lentivirus vector. The LPDS system was produced by subcloning firefly and Renilla CDS into pcDNA3.1 vector.…”
Section: Discussionmentioning
confidence: 99%
“…6 REGγ is involved in the regulation of aging via p53 and regulates lipid metabolism via Sirt1 degradation. 11 REGγ also affects angiogenesis by regulating PKA activity. 12 REGγ is conserved in Drosophila and one Drosophila Reg (identified as dReg) has been identified.…”
mentioning
confidence: 99%
“…The REGγ gene is located in 17q21 in humans, a region with high genetic linkage to schizophrenia in Latino populations (Escamilla et al, 2009;Lewis et al, 2003) and implicated in several other CNS diseases, such as autism (Cantor et al, 2005), and bipolar disorder (Ewald et al, 2005), which share at least some symptoms with schizophrenia and schizoaffective disorders. Since the discovery of a mammalian target of REGγ, SRC3 (Steroid receptor co-activator protein; Li et al, 2006), accumulating evidence has revealed diverse functions for the ATP-and ubiquitin-independent REGγ-proteasome pathway, including regulation of cell cycle (Kobayashi et al, 2013;Li et al, 2007), angiogenesis (Liu et al, 2014), and hepatic lipid metabolism (Dong et al, 2013). REGγ is widely expressed in tissues , especially in the brain.…”
Section: Introductionmentioning
confidence: 99%